Molecular Docking and ADMET Analysis of Flavonoid Compounds from Bajakah Tampala Stem (Spatholobus littoralis Hassk.) Targeting VEGFR-2 and c-MET - Ismail, Dzava Prawinsyah Fairus; Shafa, Nafis; Pendy, Violent Irene; Devon, George Patrick; Yun, Yenny Febriani (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2025)
Cancer is a condition marked by abnormal and uncontrolled cell growth, with VEGFR-2 and c-MET receptors contributing to tumor angiogenesis, metastasis, and resistance to therapy. Bajakah tampala stem (Spatholobus littoralis Hassk.) is a traditional plant from Kalimantan that is rich in flavonoid compounds that may interact with these molecular targets. This study aimed to evaluate the molecular interactions, drug-likeness, and pharmacokinetic properties of Bajakah flavonoid compounds through in silico approaches. Lipinski's rule of five and ADMET predictions indicated favorable drug-likeness and absorption profiles for most compounds, although some displayed moderate intestinal absorption and potential mutagenicity. Among the evaluated compounds, hesperetin showed the most favorable predicted binding affinity toward VEGFR-2 (binding energy -9.57 kcal/mol; predicted Ki 97.00 nM), while apigetrin demonstrated the lowest predicted binding energy toward c-MET (-9.43 kcal/mol; predicted Ki 122.94 nM). Both compounds exhibit interactions comparable to reference drugs cabozantinib and crizotinib, suggesting their potential as natural lead compounds for anticancer therapy. Further in vitro and in vivo studies are warranted to confirm their efficacy and safety.